Identidades na aula de língua inglesa em uma escola pública: uma perspectiva decolonial - Santos, Rafaella Machado dos (2019)
Grounded on the decolonial perspective and with the contribution of theoretical methodological studies in Critical Applied Linguistics, the purpose of this research is to problematize the crossings present on the processes of identities construction, via the English language teaching and learning. Placed in postmodernity, the decolonial perspective problematizes the myth of modernity, which supports the colonial structures of power and knowledge. Presented as a possibility to break with the hegemonic narratives, it questions the ways in which knowledge that is considered valid is produced, so that the historically oppressed ones can finally tell their own stories. Through a participatory action research that uses some autoethnography characteristics, this research is engaged in listening and legitimizing the students’ individual experiences, we suggest a critical analysis on their processes of identification and subjetification, which are constituted amidst conflicts inherent to the social practices, in a globalized context dominated by the English language. The purpose is to generate transformation in oneself provided by another conception of who the Other is, facilitated through a pedagogical project that presents the potential to raise questions about our multiple and decentered identities, and about how we understand differences. Conceiving the language as a social factor - without denying the context and the social and historical conditions for speech production - is a resistance stance against the structural impositions of values on our systems of representation, which are produced under unequal power relations. Such relations marginalize those who do not fit into a pre-established norm and, therefore, intend to produce truths about individuals.